Gibran Rakabuming Raka's Impression Management Strategy as a Muslim During The 2024 Presidential Election Campaign Through The Instagram Account @gibran_rakabuming - Dafuyatur Rurojifah; Muhammad Misbahuddin; Khafidhoh (Civiliza Publishing, 2025)
his study examines Gibran Rakabuming Raka's impression management strategy through Instagram during the 2024 Presidential Election campaign. As the youngest vice presidential candidate and President Jokowi's son, Gibran strategically leveraged @gibran_rakabuming platform to build an image as a dynamic young Muslim leader who was close to the people. Using a qualitative approach with the method of cultural anthropology, this study focuses on two main aspects: Gibran's impression management strategy as a young Muslim and da'wah messages through Islamic symbols in its content. The results showed that Gibran applied three main impression management tactics: ingratiation to build a likable impression, self-promotion to promote self-ability, and exemplification to show positive behavior. Interestingly, Gibran avoided the strategies of supplication and intimidation, choosing a completely positive and constructive approach. The analysis of Islamic symbols in his uploads during the campaign shows the strategic use of religious elements as a medium for da'wah. Fashion symbols (cocoa shirts, sarongs, peci, turbans) represent the simplicity and identity of Indonesian Muslims, while action symbols (kissing the hands of ulama, bowing down) reflect the morality of respect. The symbol of the place (mosque, Islamic boarding school) shows an attitude of appreciation for the crucial places for Muslims, the temporal symbol (the celebration of special days) shows that this overall strategy serves to build an emotional connection with Muslim voters and provide religious validation in the Indonesian political context.